INTERAKSI SOSIAL GURU DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 4 METRO - Hendy Pridako; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
At the time of the learning process a teacher has a high creativity and there should be interaction during the learning process, so that learners who follow the learning process is interested and not bored. The research objectives are a. To know the social interaction of teachers in history learning at SMA N 4 Metro, b. To describe teacher constraints in learning history at SMA N 4 Metro, c. To describe the teacher's efforts to overcome obstacles while interacting with students in SMA N 4 Metro. The method used in this research is observation, interview, literature, and documentation. When interacting to the learners the teacher always gives the spirit to learn, so that the mindset of these learners can slowly change the better and the learning process according to what is desired.Here's how teachers to interact with learners in learning history class X SMA Negeri 4 Metro, as follows: a. Establish good communication early in class, b. Provide motivation in the learning process in the classroom, c. Provide advice to learners in order to establish good communication. Here are the constraints or difficulties of teachers in learning history in class X SMA Negeri 4 Metro, as follows: a. When teachers interact with learners sometimes learners busy chatting outside learning materials, b. When the teacher explains the learner's material instead of playing HP so as not to focus while the learning takes place, c. Learners do not focus during the daytime due to drowsiness, hunger, and fatigue. How teachers overcome obstacles encountered as follows: a. Provide questions to students who are noisy in the classroom. b. Learners who do not pay attention to being rebuked directly.